2015
DOI: 10.1371/journal.pone.0123601
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Adipokines in the Joint. Differential Expression in Healthy and Osteoarthritis Tissues

Abstract: ObjectivesEmerging data suggest that several metabolic factors, released mainly by white adipose tissue (WAT) and joint tissues, and collectively named adipokines, might have a role in the pathophysiology of OA. Recently, novel adipokines such as SERPINE2, WISP2, GPNMB and ITIH5 have been identified in WAT. The main goal of this study was to analyse the expression of these novel adipokines in synovium, infrapatellar fat pad and chondrocytes and to compare the expression of these molecules in healthy and OA tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Additionally, leptin can directly induce the expression of MMPs, such as MMP‐1, MMP‐3, and MMP‐13 in human OA cartilage via activation of nuclear factor (NF)‐κB, protein kinase PKC and MAP pathways . The cartilage‐degrading processes could be perpetuated by leptin by induction of vascular cell adhesion molecule (VCAM)‐1 expression, an adhesion molecule responsible for leukocyte and monocyte infiltration at inflamed joints . Altogether, these data highlight the pro‐inflammatory and catabolic role of leptin on cartilage metabolism.…”
Section: Leptinmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, leptin can directly induce the expression of MMPs, such as MMP‐1, MMP‐3, and MMP‐13 in human OA cartilage via activation of nuclear factor (NF)‐κB, protein kinase PKC and MAP pathways . The cartilage‐degrading processes could be perpetuated by leptin by induction of vascular cell adhesion molecule (VCAM)‐1 expression, an adhesion molecule responsible for leukocyte and monocyte infiltration at inflamed joints . Altogether, these data highlight the pro‐inflammatory and catabolic role of leptin on cartilage metabolism.…”
Section: Leptinmentioning
confidence: 96%
“…This adipokine could be produced by synovial fibroblasts, IPFP, osteophytes, cartilage, and bone tissues within the joint . In OA cartilage and in human primary chondrocytes, adiponectin led to the increased production of NO, IL‐6, IL‐8, VCAM‐1, tissue inhibitor of metalloproteinases (TIMP)‐1, MMP‐1, ‐3, and ‐13 . However, a protective role for adiponectin in the OA pathogenesis was also been suggested.…”
Section: Adiponectinmentioning
confidence: 99%
“…Moreover, four new adipokines were found to be expressed in the IFP: serpin peptidase inhibitor (SERPINE2), WNT1 inducible signaling pathway protein 2 (WISP2), glyco‐clade E member 2 protein (transmebrane) nmb (GPNMB), and inter‐alpha‐trypsin inhibitor heavy chain family member 5 (ITIH5) (Conde et al, ). In particular, Conde et al () demonstrated an up‐regulation of WISP2 gene expression in IFP of OA patients compared to healthy controls. WISP2 is a protein involved in WNT pathway expressed by fibroblasts, mesenchymal stem cells, and adipogenic precursor cells (Grunberg et al, ).…”
Section: Obesity and Related Comorbidities In Koamentioning
confidence: 99%
“…As reported, WNT16 supported the homeostasis of progenitor cells in OA, while WNT16‐deficient mice developed more severe OA with lubricin downregulation and increased chondrocyte apoptosis . The expression of inter‐alpha inhibitor H5 (ITIH5) differed significantly between OA synovial tissues and healthy tissues . Lipoprotein receptor‐related protein 1 (LRP1) could inhibit tumour necrosis factor (TNF)‐α‐induced apoptosis and inflammation in chondrocytes .…”
Section: Discussionmentioning
confidence: 78%
“…17 The expression of inter-alpha inhibitor H5 (ITIH5) differed significantly between OA synovial tissues and healthy tissues. 18 Lipoprotein receptor-related protein 1 (LRP1) could inhibit tumour necrosis factor (TNF)-α-induced apoptosis and inflammation in chondrocytes. 19 The reduced expression of secreted frizzled related protein 1 (SFRP1) increased the activation of the Wnt/β-catenin signalling and rendered the articular cartilage prone to premature.…”
Section: Discussionmentioning
confidence: 99%